Optimasi Hidroksipropil Metilselulosa dan Polivinil Pirolidon dalam Sediaan Mucoadhesive Buccal Film Diltiazem Hidroklorida - Lusia Oktora Ruma Kumala Sari; Septi Sudianingsih; Yudi Wicaksono (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Diltiazem HCl is a class of benzodiazepine calcium channel blockers used to treat angina pectoris, arrhythmias, and hypertension. Diltiazem HCl improves first-pass metabolism, a short half time of 3-5 hours, and bioavailability of diltiazem for oral administration of about 40%. Mucoadhesive buccal film diltiazem HCl releases the drug to the buccal mucosa, so the first pass metabolism can be avoided because of its absorption through the venous system that flows from the cheek. This study aimed to study HPMC polymers and polyvinyl pyrrolidone (PVP) polymers on swelling index, residence time, mucoadhesive strength of mucoadhesive buccal film diltiazem HCl, FTIR, and drug release. The prepared film was evaluated for swelling index, mucoadhesive strength, and mucoadhesive residence time. The optimal amount for HPMC was 35 mg, and PVP was 15 mg. The combination of polymers with this amount can produce a swelling index was 3,00, mucoadhesive strength was 41,87 gF, and mucoadhesive residence time was 330,66. FTIR test indicated that there was no interaction between active function clusters of Diltiazem HCl and other excipients. The release of the optimum formula in the 360th minute was about 97.847%, following in the zero-order release model and Higuchi.